2012
DOI: 10.1155/2013/862651
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Activity of 3‐Cyano‐4‐imino‐9‐methoxy‐4H‐pyrimido [2, 1-b] pyrimido [4, 5-b] quinoline and 2‐Substituted Derivatives

Abstract: The 2-amino-7-methoxypyrimido[4,5-b]quinoline (1) on treatment with bis(methylthio)methylene malononitrile (2) in ethyl alcohol and catalytic amount of TEA gives 3-cyano-4-imino-9-methoxy-2-methythio-4H-pyrimido[2,1-b]pyrimido[4,5-b]quinoline (3). The latter were further reacted with selected N-, O-, and C-nucleophiles such as aryl amines, hetryl amines, substituted phenols, and compounds containing an active methylene group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…However, more research is necessary to confirm their efficacy and safety in this context. The study reported by Vartale et al [5] evaluated the antifungal and antibacterial activity of the tetracyclic compounds 29-33 (Table 8) using the paper disc diffusion method. The compounds exhibited varying degrees of activity against the tested fungi (A. flavus and A. niger) and bacteria (E. coli and B. subtilis).…”
Section: Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more research is necessary to confirm their efficacy and safety in this context. The study reported by Vartale et al [5] evaluated the antifungal and antibacterial activity of the tetracyclic compounds 29-33 (Table 8) using the paper disc diffusion method. The compounds exhibited varying degrees of activity against the tested fungi (A. flavus and A. niger) and bacteria (E. coli and B. subtilis).…”
Section: Compoundsmentioning
confidence: 99%
“…[1][2][3] The true potential of quinolines lies in their remarkable range of biological activities, encompassing applications as analgesics, antiemetics, trypanocidal, antiseptics, and anti-serotonin agents. [4][5][6][7] Additionally, they hold promise in various therapeutic areas, including antimalarials, antituberculars, antibacterials, antihistamines, anti-neurodegeneratives, anticonvulsants, antitumor and anticancer agents, and antiallergics. [8][9][10] This diverse spectrum of potential applications underscores the ongoing interest and exploration of quinolines in the realm of medicinal chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…12 Pyrazoles are biologically active compounds which have a broad spectrum of biological activities involving antifungal, antitubercular, anti-inflammatory activities, 13,14 analgesic agents 15 as well as their antidepressant and anticonvulsant activities. 16 The synthesis of 3-amino-5-(methylthio)-1-phenyl-1H-pyrazole-4-carbonitrile and ethyl-5-amino-3-(methylthio)-1phenyl-1H-pyrazole-4-carboxylate 17 were achieved from the reaction of phenyl hydrazine with 2-bis(methylthio)methylene)malononitrile and ethyl 2-cyano-3,3bis(methylthio)acrylate, respectively. 1,2,4-Triazole-5-thiones were prepared from refluxing either glycine hydrazide or hydrazine hydrate with different isothiocyanates in 10% K2CO3.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazolo [1,5-c]quinazoline derivatives are very important heterocyclic compounds and have been widely used as antiviral agents (Radl and Zikan, 1987), antimicrobial agents (Vartale et al, 2006), optical brighteners (Gold, 1971), dyestuffs (Rangnekar and Puro, 1990;Tsai and Wang, 2005) and colorants (Gondek et al, 2007b) and in photoluminescence (Całus et al, 2007) and electroluminescence (Gondek et al, 2007a) studies.…”
Section: Introductionmentioning
confidence: 99%